2010
DOI: 10.1016/j.sdentj.2010.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Survey of perceived stress-inducing problems among dental students, Saudi Arabia

Abstract: Female students had higher mean overall problem scores compared to male students, and second-year students showed lower perceived problems compared to other students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
77
5
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(105 citation statements)
references
References 13 publications
14
77
5
2
Order By: Relevance
“…The following three parameters were measured: (i) demographic characteristics; (ii) perceived sources of stress, using a modified DES questionnaire; and (iii) burnout, using the Maslach Burnout Inventory (MBI). The DES [4] and MBI [24] questionnaires are validated instruments. Demographic characteristics included home language as a proxy of ethnicity, in view of the 11 official languages in SA.…”
Section: Instrument and Data Collectionmentioning
confidence: 99%
See 4 more Smart Citations
“…The following three parameters were measured: (i) demographic characteristics; (ii) perceived sources of stress, using a modified DES questionnaire; and (iii) burnout, using the Maslach Burnout Inventory (MBI). The DES [4] and MBI [24] questionnaires are validated instruments. Demographic characteristics included home language as a proxy of ethnicity, in view of the 11 official languages in SA.…”
Section: Instrument and Data Collectionmentioning
confidence: 99%
“…[1,[3][4][5]9,10,12,13,16,17] The study load, financial responsibilities, patients being late or missing appointments, and fear of being unable to catch up with clinical requirements were also noted among US dental hygiene students. [20] At least two stressors in the top five of each component of the DES questionnaire posing a 'huge problem' in this study were also reported by Saudi Arabian dental students.…”
Section: Student Response To the Des Statementsmentioning
confidence: 99%
See 3 more Smart Citations